Determination the fossils content and some physical and chemical characteristics of Bab – Janah clay formation North west Syria - غادة محمد,; سوسن هيفا , (Latakia University Journal -Biological Sciences Series, 2024)
This study led to determine the source rocks characteristics of Bab Jana Formation North – West Syria. This study showed that the relationship between soil characteristics and source rocks have a vast impact on source rocks characteristics. Three locations have been chosen (Depth 0 – 30 cm); Khrbet – Alsindian, Al-Qadmous, And Wadi - Alion. Sedimentological and paleontological studies were done at the laboratories of geology department, Faculty of Sciences – Tishreen University. Some physical and chemical analyzes were also conducted on these samples , the most important of which are: (pH, EC, Total organic matter, Total CaCO3, and soil mechanical composition) in the Department of Soil and Water Sciences – Faculty of Agricultural Engineering – Tishreen University. The source rocks of these soil are composed of olive green fine – grain clay and marble, which are rich of products of the corruption of the basalt castings that lie above them, rich in residues of microorganisms, mainly foraminifera. Physical and chemical analysis showed that these soils were formed from calcite rocks heavy in texture) clay (, with a high pH level.